Investigation of the dynamic mechanical properties of epoxy resins modified with elastomers. (1st June 2016) - Mansour, G.; Tsongas, K.; Tzetzis, D.
Abstract: The mechanical and modal properties of epoxy resin reinforced with different content of carboxyl-terminated butadiene acrylonitrile copolymer (CTBN) rubber were investigated in this paper with an analytical-experimental identification method. Mechanical tensile tests were conducted for concentrations between 0 and 25wt% of CTBN rubber. The dynamic responses of the epoxy/CTBN rubber composites were measured by vibrating cantilever beam specimens with an impact force through a modal hammer, while the vibratory response was detected through an acceleration transducer. The analytical-experimental transfer function method is utilized for the deduction and therefore comparison of the elasticity modulus of the epoxy/rubber composites. The procedure for the identification of analytical-experimental transfer functions was carried out using a genetic algorithm (GA) by minimizing the difference between the measured response from tests and the calculated response, which is a function of the modal parameters. Both tensile and modal tests have shown, while it was evident from the results that the CTBN composites could absorb greater amounts of strain energy. The modal test results indicate that CTBN rubber particles can improve the damping capacity of the epoxy-based composites. However, it was observed that the stiffness of the epoxy/CTBN rubber composites was dramatically reduced.